Bacillus toyonensis biovar Thuringiensis: A novel entomopathogen with insecticidal activity against lepidopteran and coleopteran pests - Sauka, Diego Herman (2022)
The Bacillus cereus group includes eight species: Bacillus anthracis, B. cereus, Bacillus cytotoxicus, Bacillus mycoides, Bacillus pseudomycoides, Bacillus thuringiensis, Bacillus weihenstephanensis and Bacillus toyonensis, which are highly related at the phylogenetic level. In this work, we performed the isolation and characterization of a novel Bacillus sp. strain exhibiting parasporal crystals with insecticidal activity that was initially classified as a Bacillus thuringiensis strain. Its genome encoded three genes showing homology to known pesticidal proteins from B. thuringiensis and Lysinibacillus sphaericus proteins: Cry7Ga1 (a crystal protein), a Mpp2Aa3 (ETX/Mtx2 family) homolog and a mosquitocidal-like protein (NPP1). However, since its genome sequence shared > 98% ANI with several Bacillus toyonensis genomes, the strain has subsequently been renamed as Bacillus toyonensis biovar Thuringiensis and designated Bto-UNVM_94. Bioassays demonstrated that this novel strain exhibited toxicity against Cydia pomonella (Lepidoptera: Tortricidae) and Anthonomus grandis (Coleoptera: Curculionidae), a low toxicity against Aedes aegypti (Diptera: Culicidae) and Alphitobius diaperinus (Coleoptera: Tenebrionidae) whereas no toxicity was shown to the free-living nematode Panagrellus redivivus (Rhabditida: Panagrolaimidae).